2018
DOI: 10.1080/17434440.2018.1456334
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Impella and mechanical devices in cardiogenic shock

Abstract: Cardiogenic shock (CS) is a life-threatening condition associated with significant morbidity and mortality. The Impella (Abiomed Inc.) is an axial flow pump on a pigtail catheter that is placed across the aortic valve to unload the left ventricle by delivering non-pulsatile blood flow to the ascending aorta. It is used for high-risk percutaneous coronary intervention and CS. Areas covered: Percutaneous mechanical support devices are placed in a minimally invasive manner and provide life-saving assistance. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The Impella CP and IABP are commonly used mechanical support devices with each having a unique operational paradigm. The Impella is an axial flow percutaneous ventricular assist device positioned across the aortic valve that propels blood antegrade into the aorta to directly offload the LV throughout the cardiac cycle 28‐30 . In contrast, IABP counterpulsation unloads the LV indirectly through decreasing afterload during systole to promote LV ejection 18,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The Impella CP and IABP are commonly used mechanical support devices with each having a unique operational paradigm. The Impella is an axial flow percutaneous ventricular assist device positioned across the aortic valve that propels blood antegrade into the aorta to directly offload the LV throughout the cardiac cycle 28‐30 . In contrast, IABP counterpulsation unloads the LV indirectly through decreasing afterload during systole to promote LV ejection 18,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The Impella CP is a 9‐Fr catheter‐mounted microaxial rotary blood pump (14 Fr) designed for temporary MCS of less than or equal to 6 h in patients undergoing high‐risk PCI and less than or equal to 4 days for patients with cardiogenic shock 3 . The device can provide up to 4.3 L/min of flow and is inserted percutaneously via the femoral artery 14 . The Impella 5.0 and LD are both 9–Fr catheter‐mounted microaxial rotary blood pumps (21 Fr) designed for temporary MCS of less than or equal to 14 days in patients with cardiogenic shock 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The Impella 5.0 and LD are both 9–Fr catheter‐mounted microaxial rotary blood pumps (21 Fr) designed for temporary MCS of less than or equal to 14 days in patients with cardiogenic shock 3 . Both the Impella 5.0 and LD can provide up to 5.0 L/min of flow and were inserted directly through a 10‐mm vascular graft 14 . The Impella 5.0 is inserted via a cutdown of either the femoral or axillary artery and the Impella LD is inserted into the ascending aorta via an open chest procedure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All Impella pumps, except the Impella 5.0 can be inserted percutaneously into the femoral artery and create a non-pulsatile, forward flow into the aorta. Previous studies have shown that Impella improves MAP [1], reduces LV-Load, end-diastolic pressure, oxygen consumption and myocardial work [2]. The ISAR-SHOCK Trial showed that Impella provided numerous hemodynamic improvements including cardiac index, cardiac output, MAP 30 minutes after implantation with reversal of serum lactate values [3].…”
Section: Introductionmentioning
confidence: 98%